Managing change: geotechnical insights and learning from caving operations - Lett, J; Walls, J (Caving 2026: Proceedings of the Sixth International Conference on Block and Sublevel Caving, 2026)
Between the design and operational phases of a caving project, sites will typically experience variance from the plan resulting from geotechnical factors. During early construction and cave establishment, unexpected geotechnical conditions will be encountered; these may be due to a major geotechnical event, new geotechnical information or revised interpretation of design and performance criteria, each of which has the potential to impact the overall mine design and mining schedule. These variations and adaptations are disruptive, with an adverse effect on the efficiency of the operation. The changes are equally necessary to ensure personnel safety and optimal and sustainable extraction. Learnings shared in this paper include examples of instances where geological knowledge was key to determining the root cause of the geotechnical event, combined with data from geotechnical monitoring systems to ensure suitable decision-making is undertaken to mitigate from events such as rockfall, variations to rock mass conditions and caveability of high-strength lithological domains in shallow low-stress environments requiring hydraulic fracturing processes. This paper provides examples where geotechnically driven design changes were required to re-establish operations or recover from unforeseen geotechnical events. Examples from sublevel caving and block caving are discussed to demonstrate how limited early data can result in major consequences during cave establishment and conversely how, during production, a lack of knowledge can trigger major geotechnical instability that impacts safety and production of a caving operation. Cases presented in this paper comprise groundwater characterisation and the operational impact for a sublevel cave operation from suboptimal planning for handling underground water ingress, operational practices associated with close-out of working ends between crew changes and the consequential impact on downstream ground stability, shortfalls in upfront analysis and the impact on airblast risk for a block caving operation, among others.